2007
DOI: 10.1017/s146239940700035x
|View full text |Cite
|
Sign up to set email alerts
|

Rearrangements of the Williams–Beuren syndrome locus: molecular basis and implications for speech and language development

Abstract: The Williams-Beuren syndrome (WBS) locus on human chromosome 7q11.23 is flanked by complex chromosome-specific low-copy repeats that mediate recurrent genomic rearrangements of the region. Common genomic rearrangements arise through unequal meiotic recombination and result in complex but distinct behavioural and cognitive phenotypes. Deletion of 7q11.23 results in WBS, which is characterised by mild to moderate intellectual disability or learning difficulties, with relative cognitive strengths in verbal short-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
60
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(62 citation statements)
references
References 104 publications
1
60
0
1
Order By: Relevance
“…Using FISH and quantitative real time PCR, the size of the duplication was calculated generally to be the same size as of the common deletion region in WBS (~1.5 Mb). The breakpoints occur within the LCR blocks B cen and B mid with an increased expression of the genes within the single copy region of WBS [110,111]. Smaller and larger duplication sizes have also been reported [111,117,118].…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Using FISH and quantitative real time PCR, the size of the duplication was calculated generally to be the same size as of the common deletion region in WBS (~1.5 Mb). The breakpoints occur within the LCR blocks B cen and B mid with an increased expression of the genes within the single copy region of WBS [110,111]. Smaller and larger duplication sizes have also been reported [111,117,118].…”
mentioning
confidence: 90%
“…So far, only a few cases of duplications have been described in the literature. The clinical presentation associated with reciprocal WBS duplications certainly seems to be milder, and facial features are different and less distinct than those of WBS; thus, presumably more patients exist but remain undiagnosed [103,110,118,119].…”
mentioning
confidence: 99%
“…[1][2][3][4] This region frequently undergoes genomic rearrangements due to the presence of low copy repeats flanking the commonly deleted region and results in meiotic nonallelic paralogous recombination. 1 Consistently, along with the 7q11.23 deletion, recent papers reported the reciprocal duplication 5,6 and inversion 7,8 of the region. WBS has a prevalence estimated between 1/7500 and 1/20 000.…”
Section: Introductionmentioning
confidence: 86%
“…Their phenotypic features vary from isolated SVAS to classic WBS associated with infantile spasms or with autism spectrum behavior. 5,14,15 Genotypephenotype correlation studies of these patients suggested important insights in the genetic causes of some of the typical WBS symptoms. So far, the strongest correlations have been found for some of the facial features and cardiovascular problems linked to elastin haploinsufficiency.…”
Section: Introductionmentioning
confidence: 97%
“…The deletion occurs between proximal and medial LCRs in about 95% of WBS cases, and it occurs between proximal and distal LCRs in the remaining cases. The size of the deletion is approximately 1.55 Mb for the small deletion and approximately 1.84 Mb for the larger one [1][2][3][4][5]. However, the precise size depends upon the exact position of the breakpoints in each block.…”
Section: Introductionmentioning
confidence: 99%